Do Hospitals with a Higher Level of Maternal Care Designation Have Better Maternal Outcomes? - Srinivas, Sindhu K.; Kozhimannil, Katy; Hung, Peiyin; Attanasio, Laura; Jou, Judy; Grobman, William A. (American Journal of Perinatology, 2019)
Background A recent document by the American Congress of Obstetricians and Gynecologists (ACOG) and the Society for Maternal-Fetal Medicine introduced the concept of uniform levels of maternal care (LMCs).Objective We assessed LMC across hospitals and measured their association with maternal morbidity, focusing on women with high-risk conditions.Study Design We collected data from hospitals from May to November 2015 and linked survey responses to Statewide Inpatient Databases (SID) hospital discharge data in a retrospective cross-sectional study of 247,383 births admitted to 236 hospitals. Generalized logistic regression models were used to examine the associations between hospitals' LMC and the risk of severe maternal morbidity. Stratified analyses were conducted among women with high-risk conditions.Results High-risk pregnancies were more likely to be managed in hospitals with higher LMC (p < 0.001). Women with cardiac conditions had lower odds of maternal morbidity when delivered in level I compared with level IV units (adjusted odds ratio: 0.29; 95% confidence interval: 0.08–0.99; p = 0.049). There were no other significant associations between the LMC and severe maternal morbidity.Conclusion A higher proportion of high-risk pregnancies were managed within level IV units, although there was no overall evidence that these births had superior outcomes. Further prospective evaluation of LMC designation with patient outcomes is necessary to determine the impact of regionalization on maternal outcomes.
Keywords: maternal morbidity; levels of care; regionalization; maternal outcomes